Efeitos da paisagem marinha nas populações de peixes de interesse comercial - Verba, Júlia Tovar (2019)
Fisheries science is characterized by several knowledge gaps that prevent the development of more sound research for fish stock conservation. Understanding how these stocks are spatially distributed and which genetic and environmental characteristics explain this distribution is crucial for fishery planning. In this thesis we describe exploitation status, population genetic structure and connectivity, and effective population size of commercially important marine fish in Brazil. The first chapter presents an analysis of catch data for 132 species for 61 years. The results indicate a interaction between climatic, biological and fishery factors affecting the species collapsing risk. In the second chapter, we identified the population genetics structure and historical demography for 17 species. Most species presented a lack of environmental barriers to gene flow along the Brazilian coast. However, population structure of Pomatomus saltatrix and Cynoscion jamaicensis results indicate genetic discontinuity due to temperature changes and isolation by distance, respectively. The goal of the third chapter was to identify effective population size variability for two reef species – Lutjanus jocu and Sparisoma axillare – and test the influence of past climatic variability on population size changes. Sparisoma axillare population expanded until five thousand years ago and is mostly stable until today, with a population expansion justified by increase in suitable habitat. For Lutjanus jocu, results suggest that, after a period of population expansion, is has been stable for the last one million years. Habitat suitability for L. jocu is apparently stricter nowadays than in the past, but this change does not seem related to population size. Distribution range of L. jocu is larger than S. axillare (endemic to Brazil), so it might be less susceptible to regional climatic changes. In the fourth chapter, we identified which seascape characteristics explain genetic connectivity patters of S. axillare, in the Brazilian coast and the islands of Fernando de Noronha, Abrolhos and Trindade. The results indicate that only Trindade Island population is genetically distinct. We found that seascape factors, as bathymetry and oceanic currents, can be more important to explain genetic variation than geographical distance. The results of this thesis suggest that some environmental variables affect species conditions: temperature can positively affect some stocks, but species vulnerable to warmer temperatures can collapse; S. axillare seems to be sensitive to changes in habitat availability, and depth and oceanic currents influence population connectivity of this species with vulnerable characteristics, making an isolated population even more at risk.